Gender Disparities and Burnout Among Emergency Physicians: A Systematic Review by the World Academic Council of Emergency Medicine–Female Leadership Academy for Medical Excellence - Suman Thakur; Vivek Chauhan; Sagar Galwankar; Fatimah Lateef; Pia Daniel; Zeynep Cakir; Katia M. Lugo; Samjhana Basnet; Busra Bildik; Siham Azahaf; Sevilay Vural; Busra H. Difyeli; et al. (Western Journal of Emergency Medicine)
Background: The Female Leadership Academy for Medical Excellence, members of the World Academic Council of Emergency Medicine, conducted this systematic review, which explores gender disparities in burnout among emergency physicians (EP) using the Maslach Burnout Inventory-Human Services Survey (MBI-HSS). Burnout is a critical issue in healthcare, particularly in emergency medicine where high stress and demanding work environments prevail. Methods: Following PRISMA guidelines, we searched PubMed and Epistemonikos for studies using MBI-HSS to measure burnout in EPs. Inclusion criteria encompassed peer-reviewed, English-language articles reporting burnout by sex. Data extraction focused on proportions of burnout and its subcomponents, mean scores, and odds ratios, with quality assessed using Joanna Briggs Institute criteria. Results: We included 18 studies spanning 26,939 EPs from 10 countries. While overall burnout rates did not significantly differ between the sexes, the proportion of female EPs with high emotional exhaustion (EE) (69%) and low sense of personal accomplishment (PA) (45%) were significantly higher compared to males with high EE in 57% and low PA in 29%, respectively (P < 0.001 for both). Proportion with high depersonalization (DP) score was 44% in both male and female EPs. Mean scores revealed females experiencing higher mean EE (26.8 ± 15.7) scores vs males (25.4 ± 15.9) P < 0.001. Males had mean DP scores (8.6 ± 8.0) and mean PA scores (26.6 ± 12.7) compared to females with lower mean DP scores (7.4 ± 7.2) and higher PA scores (27.7 ± 11.9), respectively P < 0.001 for both. Odds ratios indicated varying risks, predominantly higher EE odds among females, varying from 0.72 to 2.3. Conclusion: This review underscores gender-specific manifestations of burnout among emergency physicians, with females more susceptible to emotional exhaustion and lower sense of personal accomplishment. Standardized reporting methods are crucial for future meta-analyses to refine gender-specific interventions combating burnout in emergency medicine. Targeted strategies addressing distinct manifestations of burnout are imperative to support the well-being and retention of EPs, fostering sustainable healthcare delivery.